On-Demand Programming Assistance - Chen, Yan; Jones, Jasmine; Oney, Steve (2020)
ABSTRACT Many teams have shifted to online remote collaboration as a result of COVID-19, from professional development teams to programming classes to computing-related workspaces (e.g., makerspaces). This paper explores on-demand remote help seeking in programming, a type of collaboration that occurs when developers seek online support for their tasks as needed, and argues that a key challenge in scaling remote on-demand collaboration in programming is to facilitate effective context capturing and workforce coordination. Traditionally, this collaboration happens within teams and organizations where people are familiar with the context of the tasks. Recently, this collaboration has become ubiquitous due to the success of paid online crowdsourcing marketplaces (e.g., Upwork) and Q&A sites (e.g., Stack Overflow). We discuss prior work on on-demand collaboration in programming, analyze how the idea can be tested in physical computing as well, and examine existing and new challenges that should be further explored. Keywords on-demand support; programming collaboration; crowdsourcing ABOUT THE AUTHOR/S YAN CHEN University of Michigan yanchenm@umich.edu I am a PhD candidate at University of Michigan. My research aims to leverage human computation and machine intelligence to effectively solve complex tasks that require domain expertise, such as software development. I study problems that users face during collaboration with existing tools and methods, and build computational systems to assist users via efficient collaboration and hybrid crowd-machine workflow. [https://chensivan.github.io/] JASMINE JONES Berea College drjaztech@gmail.com Dr. Jasmine Jones specializes in Human-Computer Interaction, focusing on the study and design of embedded interactive systems in social contexts. Her prior work addresses design for value-sensitive scenarios, such as capturing family memories, communicating children’s health information, and self-tracking behaviors in recovery. Dr. Jones is excited to develop new courses in user-centered design and human-centered computing to guide students in creating useful and usable new technologies. STEVE ONEY University of Michigan soney@umich.edu Steve Oney is an Assistant Professor at the University of Michigan School of Information. His research focuses on enabling and encouraging more people to write and customize computer programs by creating new programming tools and exploring usability issues in programming environments. Steve completed his Ph.D in Carnegie Mellon's Human-Computer Interaction Institute where he was advised by Professor Brad Myers and Dr. Joel Brandt. He also attended MIT (CS & math S.B. in 2007, CS M.Eng in 2008). New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).